IMPLEMENTASI ENKRIPSI URL PADA WEBSITE MENGGUNAKAN METODE BASE64 DAN ROTATION13 - Mochammad Firman Arif (SPIRIT, 2020)
Abstract: The development of technology in this era is getting faster this is unknown from the distribution of information which is also developing, the internet is one of the media of the dissemination of information that is very broad so fast. However, the services provided by each of these sites are one of several related issues: cross-site scripting, information leakage, authentication and authorization, Session management, SQL Injection, CSRF and others. Therefore based on this security issue and also some of the references above make researchers want to implement a security made with the introductory URL on the website using several encryption algorithms summarized in BASE64 and ROT13 as actions against attacks that attack the system.